2010
DOI: 10.1007/s13181-010-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prophylactic Effect of Silymarin and Deferoxamine on Iron Overload-Induced Hepatotoxicity in Rat

Abstract: In pathologic conditions or poisoning states, iron overload can affect different tissues including liver. In this study, the prophylactic effect of deferoxamine and silymarin was compared in decreasing experimental ironoverload-induced hepatotoxicity in rats. The study was done in six groups of rats, which received drugs q2 days for 2 weeks. The rats in groups 1 to 6 received drugs, respectively: normal saline, iron dextran, iron dextran+deferoxamine (intraperitoneally), iron dextran+silymarin (orally), iron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Iron chelator, DEF, is often used to treat genetic or acquired iron accumulation. By the essential characteristic of binding iron, DEF is also widely used to protect oxidative stress and reduce the damage to various organs and tissues, such as the liver . NAC is an antioxidant that provides protective effect to resist injury caused by ROS, being proven via regulation of the JNK/Bcl‐2 pathway …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron chelator, DEF, is often used to treat genetic or acquired iron accumulation. By the essential characteristic of binding iron, DEF is also widely used to protect oxidative stress and reduce the damage to various organs and tissues, such as the liver . NAC is an antioxidant that provides protective effect to resist injury caused by ROS, being proven via regulation of the JNK/Bcl‐2 pathway …”
Section: Discussionmentioning
confidence: 99%
“…By the essential characteristic of binding iron, DEF is also widely used to protect oxidative stress and reduce the damage to various organs and tissues, such as the liver. 23 NAC is an antioxidant that provides protective effect to resist injury caused by ROS, being proven via regulation of the JNK/Bcl-2 pathway. 24 In our study, we observed viability of hepatocyte spheroids stored in HTK and the addition of DEF and/or NAC.…”
Section: Albumin Production and Gene Expressionmentioning
confidence: 99%
“…Previous studies confirmed that the iron-chelating properties of a plant directly related to its flavonoids content (39). Najafzadeh et al demonstrated that silymarin as a flavonoid could decrease iron overloadinduced liver toxicity and its effects were similar to deferoxamine (40). In another study showed that baicalin (a commercial flavonoid) has iron chelating and liver protective effects in iron overload mice (36).…”
mentioning
confidence: 82%
“…27 The second condition included HTK and deferoxamine (DEF), which is known to reduce oxidative stress and tissue damage. 28 The third condition included HTK and N-acetyl-L-cysteine (NAC), a known protective antioxidant. 29 The final condition combined the three supplements, HTK, DEF, and NAC.…”
Section: Hepati C and Pan Cre Ati C Xenotr Ans Pl Antation Update Smentioning
confidence: 99%